Awareness of the general population about vocal voice hygiene - Violeta Bilinac; Ana Lončar (Биомедицинска истраживања, 2024)
Introduction: The definition of a normal voice is difficult to determine because the voice is defined by the speaker’s anatomical configuration, socialization process, and culture. However, we can define the voice as healthy or dysphonic. The aim of the research in this work was to examine the awareness of the general population about voice disorders and vocal hygiene and its impact on voice health. Method: In order to analyze the awareness of the general population about voice disorders and vocal hygiene, a cross-sectional study was conducted among 80 respondents from Foča and Podgorica. A survey questionnaire developed at the Center for Voice Health at the University of Michigan Health System was used as an instrument. Results: The research results showed that there were no significant differences between men and women regarding being informed about voice disorders and vocal hygiene. Respondents of different educational status, smoking status and age did not show significant differences in awareness about voice disorders and vocal hygiene. Conclusion: Based on the obtained results, it was shown that awareness about voice disorder and vocal hygiene was sufficient, but that it could be better.
Keywords: vocal hygiene; general population; research